2008
DOI: 10.1017/s0144686x07006927
|View full text |Cite
|
Sign up to set email alerts
|

A different story: exploring patterns of communication in residential dementia care

Abstract: This article reports findings from a three-year project on ‘Communication patterns and their consequences for effective care’ that explored communication in dementia-care settings. As the proportion of people with dementia living in British care-homes continues to grow, there is a need to understand better their care. Using a range of qualitative methods, the project set out to identify the constituent elements of dementia-care practice and the patterns that characterise day-to-day relations in care homes. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
154
2
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(167 citation statements)
references
References 31 publications
(36 reference statements)
4
154
2
3
Order By: Relevance
“…Previous research has revealed the importance of textiles and clothing in establishing and maintaining a sense of personhood (Ward et al, 2008;Ward and Campbell, 2013;Kontos and Martin, 2013). When people enter residential care they are often parted from personal possessions 'disrupting connections to memories, biography and identity' (Twigg and Buse, 2013, pp.…”
Section: Textiles and Personhoodmentioning
confidence: 99%
“…Previous research has revealed the importance of textiles and clothing in establishing and maintaining a sense of personhood (Ward et al, 2008;Ward and Campbell, 2013;Kontos and Martin, 2013). When people enter residential care they are often parted from personal possessions 'disrupting connections to memories, biography and identity' (Twigg and Buse, 2013, pp.…”
Section: Textiles and Personhoodmentioning
confidence: 99%
“…Previous studies demonstrated that there are considerably fewer interactions between staff and residents with dementia versus staff interactions with residents without dementia (Kitwood and Bredin, 1992;Ward et al, 1992;Acton et al, 2007;Ward et al, 2008). For example, residents with dementia were left alone for approximately 75% of the time; the more confused residents remained inactive for nearly 85% of the time (Hallberg et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Social interactions in long-term care settings between staff and residents with dementia have been characterized as task-oriented, patronizing, and/or overly directive (Ward et al, 2008;Williams et al, 2009;Vasse et al, 2010). Staff-resident interactions can be infrequent, short, and fragmented (Ekman et al, 1991;Kolanowski et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, it should be noted that 'assisted autonomy' is necessary to promote the agency of people with dementia (Boyle 2008). Although Sabat (2003, p. 85) had suggested that people with dementia are susceptible to 'malignant positioning' by others which can undermine their sense of social competency, it is important to note that, at times, this negative positioning may be explained more by gender inequality than by -what Ward et al (2008) referred to as -'cognitive disablism'.…”
Section: Competency and Capacitymentioning
confidence: 99%